Perencanaan Perbaikan Jalan Pada Ruas Jalan Santan - Bontang - Rosa Agustaniah (Kurva S : Jurnal Keilmuan dan Aplikasi Teknik Sipil, 2017)
In a pavement repair work, it is known the terms of maintenance and rehabilitation of the meaning is different. The boundaries that distinguish the two terms are not the same between one institution to another. Construction of road pavement from the subgrade, base course and asphalt when designed with the correct method, will provide service life as planned. The study is based on a planning analysis of road repair roads Santan-Bontang. The results of this study show the extent of damage are over-load that is under 1.00 mm specification of traffic that crosses the Santan-Bontang road and highway pavement thickness by the method of component analysis results of the calculations are ITPada> ITPrencana. The results of analysis and calculation Road Condition Index (RCI) can result asphalt pavement tables ACWC is 5.00 cm.Improvement plan is to dismantle, dig up and replace the ugly and damaged material corresponding test results and immediately carried back closure and the asphalt was broken immediately in doing the job patchy (Paching).